Multi-objective optimization design on high pressure side of a pump-turbine runner with high efficiency - Qin, Yonglin; Li, Deyou; Wang, Hongjie; Liu, Zhansheng; Wei, Xianzhu; Wang, Xiaohang (Renewable energy, 2022)
The geometry of blade high-pressure side has significant effects on the performance of pump-turbine at both design and off-design operating point. This paper presents a runner optimization strategy which especially focuses on the blade high-pressure side to increase the efficiency of design points at both pump and turbine modes. First, the concepts of “swept,” “bowed (lean),” and “twisted” are introduced to systematically widen the design space. Then, a multi-objective optimization design system consisting of geometry generation, computational fluid dynamics (CFD), design of experiment, approximation model, and a multi-objective genetic algorithm is built and the optimized plan is selected from the Pareto front of the last generation. Compared with the original runner, the optimized runner can increase the efficiency by 1.17% and 0.46% for the pump and turbine modes, respectively. Moreover, the pump mode is more sensitive to the uniform design in the spanwise direction at the high-pressure side than the turbine mode. Detailed hydraulic loss analyses and local entropy production rate analyses reveal that for both pump mode and turbine mode, the optimized runner can significantly decrease the hydraulic loss in the downstream domains of high-pressure side. The geometry of blade high-pressure side has remarkable effects on hydraulic loss and more attention should be paid in design stage.